The Influence of Mindful Attention on Value Claiming in Distributive Negotiations: Evidence from Four Laboratory Experiments - Reb, Jochen (Institutional Knowledge at Singapore Management University, 2013)
We examined the effect of mindful attention on negotiation outcomes in distributive negotiations across four experiments. In Studies 1 and 2, participants who performed a short mindful attention exercise prior to the negotiation claimed a larger share of the bargaining zone than the control condition participants they negotiated with. Study 3 replicated this finding using a different manipulation of mindful attention. Study 4 again replicated this result and also found that mindful negotiators were more satisfied with both the outcome and the process of the negotiation. We discuss theoretical and practical implications, limitations, and future directions.